Celastrol Loaded Nanoparticles With ROS-Response and ROS-Inducer for the Treatment of Ovarian Cancer - Niu, Weina; Wang, Jianguo; Wang, Qinyao; Shen, Jianjun (Frontiers in Chemistry, 2020)
Ovarian cancer is a gynecological cancer that is difficult to be completely cured. It is common to use regimens as an effective treatment for ovarian cancer, but it also inevitably brings serious side effects. New treatment strategies and special drugs are needed to improve the prognosis of patients. Celastrol, a natural product isolated from traditional medicine, has been proved curative for inflammation and cancers. However, the non-targeting and low solubility of celastrol limit its clinical application. Therefore, we prepares a celastrol-loaded nanoparticles for the efficient treatment of ovarian cancer via oxidative stress amplification. In this work, a tumor-targeted, ROS-sensitive nanoparticle is designed, synthesized and assembled into the drug delivery system of celastrol. Folic acid (FA) groups on the surface of nanoparticles guide the nanoparticles to target the surface of the tumor cell membrane actively. Thioketal (TK) bonds in nanoparticles can be oxidized and broken into -SH within the ROS level of tumor tissues, which causes the breaking of the PEG hydrophilic shell layer of nanoparticles and promotes the release of celastrol. The released celastrol further stimulated the production of ROS and amplified the intracellular ROS level to promote the apoptosis of tumor cells, thus achieving the therapeutic effect of tumor